Using Satellite Imagery to Assess Impacts of Soil and Water Conservation Measures : Evidence from Ethiopia's Tana-Beles Watershed - Ali, Daniel Ayalew (World Bank, Washington, DC, 2018)
Although efforts at soil and water conservation are routinely viewed as instrumental in reducing vulnerability to climate change, their impact has rarely been quantified. Combining data on the timing and intensity of soil and water conservation interventions in select Ethiopian watersheds from 2009 to 2016 with a pixel-level panel of vegetative cover and soil moisture data derived from satellite imagery makes it possible to assess the biophysical impacts of such measures using a difference-in-differences specification. The results point toward significant effects overall that vary by season, and that tree planting and other soil and water conservation activities are more effective on degraded than cultivated land. The results are consistent with before-after regressions for daily sediment load and stream flows in a subset of micro-watersheds. It thus appears that satellite imagery can improve the design and near-real-time monitoring of sustainable land management interventions for watersheds and landscape.